ANHEDONIA DALAM FOTOGRAFI EKSPRESI - Rachmawati, Ine; Iriani, Dewi; Mutohari, A Sobi (ASKARA: Jurnal Seni dan Desain, 2023)
The creation of this photographic work with the title Anhedonia in Expression Photography, the concept is to represent feelings that are abstract or can only be felt and imagined but do not have a form that can be seen with the naked eye. The author chose one of these abstract traits, namely anhedonia. Anhedonia is a term for a depressive condition in a person characterized by a loss of interest in enjoying pleasure in his life. Apart from being abstract, this is also based on empirical experience. Responding to this, the author has an interest in being able to represent it in expression photography. The objectives of this creation are 1) to represent abstract feelings into visual photography, 2) to create expression photography with glow in the dark technique, 3) to expand the repertoire of photographic art creation. The creation method uses a photography creation method approach into three stages, namely exploration, experimentation and final realization. The creation of this result is expected to provide one of the references in expression photography and can be developed into further research with similar theme concepts.